2015
DOI: 10.1093/nar/gkv093
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous actions of the human growth hormone long-range enhancer

Abstract: The human growth hormone (hGH) gene is controlled by a long-range enhancer, HSI, located 14.5 kb 5′ to the hGH promoter. HSI establishes a domain of noncoding transcription that is ‘looped’ to the hGH promoter as an essential step in initiating hGH gene expression. Thus, defining how HSI generates its domain of noncoding transcription is central to understanding its long-range function. Here, we demonstrate that activation of noncoding transcription reflects an HSI-autonomous activity fully independent of inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
(74 reference statements)
0
1
0
Order By: Relevance
“…These three sites play an essential role in both the activation and the maintenance of hGH1 transcription in the somatotrope (14)(15)(16)(17) and in its maintenance in the adult (18). POU1F1 binding at these LCR sites within HSI triggers the formation of an extensive (32 kb) domain of histone acetylation throughout the hGH locus (19) and is essential for bringing the LCR in close proximity ('looping') to the hGH1 promoter (20)(21)(22). It has been demonstrated that a single-base difference between POU1F1-binding sites at the hGH1 promoter and those at HSI modifies the conformation of the POU1F1/DNA complex, suggesting that these complexes may function through differential cofactor recruitment (23).…”
Section: Introductionmentioning
confidence: 99%
“…These three sites play an essential role in both the activation and the maintenance of hGH1 transcription in the somatotrope (14)(15)(16)(17) and in its maintenance in the adult (18). POU1F1 binding at these LCR sites within HSI triggers the formation of an extensive (32 kb) domain of histone acetylation throughout the hGH locus (19) and is essential for bringing the LCR in close proximity ('looping') to the hGH1 promoter (20)(21)(22). It has been demonstrated that a single-base difference between POU1F1-binding sites at the hGH1 promoter and those at HSI modifies the conformation of the POU1F1/DNA complex, suggesting that these complexes may function through differential cofactor recruitment (23).…”
Section: Introductionmentioning
confidence: 99%